Pengembangan Lembar Kerja Peserta Didik Fisika Berbasis Pendekatan Science, Technology, Engineering, and Mathematics untuk Meningkatkan Berpikir Kritis Peserta Didik - Ramli Ramli; Yohandri Yohandri; Yulis Septianas Sari; Mitri Selisne (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
Students' critical thinking skills are still not optimal. One of the reasons is the use of teaching materials in the form of student worksheets that are not yet in line with the good student worksheet structure, do not yet contain the STEM approach, and critical thinking indicators have not been clearly illustrated in the student worksheet. The purpose of this study is to determine the validity of the LKPD, determine the practicality and effectiveness of using student worksheet Physics based on the STEM approach that can improve students' critical thinking. This type of research is research and development (R&D) using the Borg & Gall model which consists of the initial research and information gathering stage, planning, developing the initial product format, and initial trials. As the object of research is the Physics student worksheet based on the STEM approach. Data collection instruments used were expert validation sheets, practicality test sheets, and effectiveness test sheets. The effectiveness test uses an assessment sheet of learning outcomes tests and observation sheets of students' critical thinking. The data analysis technique used is the analysis of the validity of the Physics student worksheet, the practicality analysis of the use of the Physics student worksheet, and the effectiveness analysis of the use of the Physics student worksheet. Based on the analysis of the data that has been done, two research results can be put forward. First, the average value of the validity of the Physics student worksheet based on the STEM approach is 0.88 and this value is included in the valid category. Second, the average value of the practicality test for the use of Physics student worksheet by teachers and students respectively 91.44 and 84.14. This value shows the Physics student worksheet is in the category of very practical. Besides that, the use of Physics student worksheet based on the STEM approach is effective to improve students' critical thinking